Problem-based learning in nurse education: an unexpected problem for students with dyslexia. - Roberts D; Mitchell D (Nurse Education in Practice, 2005)
This paper is a discussion that examines the difficulties caused by problem-based learning (PBL) in nurse education to students with dyslexia. The discussion is based on the authors' experience of implementing a curriculum based on PBL in one English University. It highlights a significant issue that might easily be overlooked as problem-based learning becomes common in nurse education. In short, this is that people with dyslexia may experience difficulties in understanding parts of the process of the method of learning as well as some of the more well known difficulties with written assessment. The paper suggests ways that PBL facilitators might be able to help reduce such difficulties for students with dyslexia.